Effect of polymorphism of Insulin-induced gene 1 (INSIG1) (A4366G) on slaughter characteristics in unproductive Kebumen Ongole Grade cows - Slamet Diah Volkandari; Saiful Anwar; Ari Sulistyo Wulandari; Pita Sudrajad; Indriawati Indriawati; Mukh Fajar Nasrulloh; Ika Rahmawati; Endang Tri Margawati; Muhammad Cahyadi (Universitas Sebelas Maret, 2021)
Objective: Kebumen Ongole Grade (Kebumen OG) are known as good performance cattle with body weight and body measurement higher than National Standard of Ongole Grade cattle. Productivity is influenced by genetic and environmental factors. Insulin-induced gene-1 (INSIG1) gene is one of many genes that are considered important in influencing carcass characteristics and playing an important role in lipid metabolism (adipogenesis and or lipogenesis). So, the aim of this study was to identify of SNP A4366G in INSIG1 gene and associated with slaughter characteristics of unproductive Kebumen OG cows.Methods: In this study used 44 unproductive Kebumen OG cows from slaughter house in Kebumen. Slaughter characteristics contain of slaughter weight, hot carcass weight and dressing percentage. Three milliliters of blood samples were collected from vena jugularis. DNA were extracted from blood samples using salting out method. Genotyping of INSIG1 gene (A4366G) used PCR-RFLP method with TaqI restriction enzyme. Genetic diversity data in this study were allele and genotype frequencies, heterozygosity, PIC and HWE. Association of genotypes of INSIG1 gene with slaughter characteristics were analyzed using ANOVA univariate model.Results: Polymorphic of INSIG1 (A4366G) gene was found in the unproductive Kebumen OG cows. Three variants of genotypes (AA, AG, GG) with two alleles (A and G) were found with allele frequencies 0.795 for G allele. The population was in equilibrium genetic. Association of slaughter characteristics with genotypes were not significant (p>0.05).Conclusions: Polymorphic of INSIG1 gene (A4366G) was found in unproductive Kebumen OG cows population with dominant of G allele. The population was in genetic equilibrium. The association of slaughter characteristics with genotype of INSIG1 gene (SNP A4366G) was not significant.